KONSEP KONSEP SAJA’ DALAM DALAM SURAH AL-MU’AWWIDZAT (KAJIAN ILMU BADI’) - Bunga Rosi; Rahmat R; Isda Sari , Rada (AL MUALLAQAT, 2022)
This research examines the concept of Saja' in Badi Sciences and Examples of Its Use in Surah Al-Mu'awwidzat. Saja' is part of the science of badi' which specifically discusses the similarity of the final letters in two fasilah or sentence structures. In the discussion alone, it is divided into four types, namely only mutharraf, only mutawazin, only mutawazi and only. In research using qualitative research with a literature review approach. Then based on the analysis conducted by the researcher, there are only a few' in surah Al-Mu'awwidzat namely in surah Al-Ikhlas there is only 'mutharraf, in surah Al-Falaq there are only 'mutharraf and only' mutawazin then in surah An-Nas there are one of a kind' that is only' mutharraf.